Subclausal Local Contexts. (3rd June 2021) - Anvari, Amir; Blumberg, Kyle
Abstract: One of the central topics in semantic theory over the last few decades concerns the nature of local contexts . Recently, theorists have tried to develop general, non-stipulative accounts of local contexts (Ingason, 2016 ; Mandelkern & Romoli, 2017a ; Schlenker, 2009 ). In this paper, we contribute to this literature by drawing attention to the local contexts of subclausal expressions. More specifically, we focus on the local contexts of quantificational determiners, e.g. 'all', 'both', etc. Our central tool for probing the local contexts of subclausal elements is the principle Maximize Presupposition! (Percus, 2006 ; Singh, 2011 ). The empirical basis of our investigation concerns some data discussed by Anvari (2018b), e.g. the fact that sentences such as 'All of the two presidential candidates are crooked' are unacceptable. In order to explain this, we suggest that the local context of determiners needs to contain the information carried by their restrictor. However, no existing non-stipulative account predicts this. Consequently, we think that the local contexts of subclausal expressions will likely have to be stipulated. This result has important consequences for debates in semantics and pragmatics, e.g. those around the so-called "explanatory problem" for dynamic semantics (Heim, 1990 ; Schlenker, 2009 ; Soames, 1982 ).